Analysis of Service Quality to Increase Customer Satisfaction at Lawson Gading Serpong Retail Stores - Magdalena; Akbar, Subhan (Journal of Social Science and Business Studies, 2023)
The purpose of this research is to find out what factors influence the level of customer satisfaction when shopping at retail. Surveys were conducted to collect data. The survey was conducted for 1 week, with a total of 30 respondents. The survey results that have been obtained are then entered into the recap file, which is then explained in more detail in the Excel file. In the Excel file, the data that has been obtained is divided into two measurement categories: importance and performance. Then calculate the gap. The results of the Gap 5 analysis show that 80% of the indicators considered important by consumers in providing satisfaction do not provide good performance. Then, in the IPA analysis, it was also found that many indicators were still lacking in terms of performance, even though their level of importance was quite high. It was concluded that Lawson, as one of the well-known retail stores, is still lacking in terms of performance.